2022
DOI: 10.3390/ijms232012614
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Profiling of Nephrotic Syndrome towards Biomarker Discovery

Abstract: Nephrotic syndrome (NS) is a kidney illness characterized by excessive proteinuria, hypoalbuminemia, edema, and hyperlipidemia, which may lead to kidney failure and necessitate renal transplantation. End-stage renal disease, cardiovascular issues, and mortality are much more common in those with NS. Therefore, the present study aimed to identify potential new biomarkers associated with the pathogenesis and diagnosis of NS. The liquid chromatography–mass spectrometry (LC–MS) metabolomics approach was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The current study has identified a broad array of fifteen altered metabolites in renal amyloidosis patients presenting with nephrotic syndrome, unlike those reported for NS in the literature 44,45 . Out of these, L-cystine and different types of carnitine levels were found to be upregulated.…”
Section: Discussionmentioning
confidence: 62%
“…The current study has identified a broad array of fifteen altered metabolites in renal amyloidosis patients presenting with nephrotic syndrome, unlike those reported for NS in the literature 44,45 . Out of these, L-cystine and different types of carnitine levels were found to be upregulated.…”
Section: Discussionmentioning
confidence: 62%
“…Metabolomics describes analyzing all metabolites (compounds with low molecular weight, generally 1,500 Da) present in a particular sample acquired from a biological system ( Patti et al, 2012 ; Dahabiyeh et al, 2020 ; Gu et al, 2020 ). Metabolomics has emerged as a potentially useful diagnostic and prognostic tool that might explain disease pathogenesis ( Masood et al, 2021 ; Jacob et al, 2022 ; Jans et al, 2022 ). There currently needs to be more investigations on the pathophysiology of GAL that concentrate on urine or blood metabolomics profiling ( Taylor Fischer et al, 2019 ; Hermans et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%